KnowledgeBoat Logo

Mathematics

Prove that : 1 + cos A1 - cos A=(cosec A + cot A)2\dfrac{\text{1 + cos A}}{\text{1 - cos A}} = \text{(cosec A + cot A)}^2.

Trigonometric Identities

1 Like

Answer

Multiplying numerator and denominator of L.H.S. of the given equation, by (1 + cos A) :

1 + cos A1 - cos A×1 + cos A1 + cos A(1 + cosA)2(1cos2A)(1 + cosA)2(sin2A)(1 + cos Asin A)2.\Rightarrow \dfrac{\text{1 + cos A}}{\text{1 - cos A}} \times \dfrac{\text{1 + cos A}}{\text{1 + cos A}} \\[1em] \Rightarrow \dfrac{\text{(1 + cos} A)^2}{(1 - \text{cos}^2 A)} \\[1em] \Rightarrow \dfrac{\text{(1 + cos} A)^2}{(\text{sin}^2 A)} \\[1em] \Rightarrow \Big(\dfrac{\text{1 + cos A}}{\text{sin A}}\Big)^2.

Solving R.H.S. of the given equation :

(cosec A + cot A)2(1sin A+cos Asin A)2(1 + cos Asin A)2.\Rightarrow \text{(cosec A + cot A)}^2 \\[1em] \Rightarrow \Big(\dfrac{1}{\text{sin A}} + \dfrac{\text{cos A}}{\text{sin A}}\Big)^2 \\[1em] \Rightarrow \Big(\dfrac{\text{1 + cos A}}{\text{sin A}}\Big)^2.

Since, L.H.S. = R.H.S.

Hence, proved that 1 + cos A1 - cos A=(cosec A + cot A)2\dfrac{\text{1 + cos A}}{\text{1 - cos A}} = \text{(cosec A + cot A)}^2.

Answered By

1 Like


Related Questions